onstructing the Role Of Storytelling in The Preservation Of Indigenous Nigerian Traditions - Ogbu, Silk Ugwu (Advances in Social Sciences Research Journal, 2018)
Since the advent of Colonialism, a real concern has been and remains the struggle to hold on to indigenous traditions and cultural identities in Nigeria and across most of Africa in the face of the crusading influence of westernization. In the view of many Afro-centric pundits, it has become imperative that decisive measures need to be taken to reverse the tide of the rapidly deteriorating cultural identity of neo-colonial African societies. These measures are especially needed in the light of the rise in criminal behavior and general moral decadence among the youths which are said to be as a result of a crisis in cultural values. This paper draws on existing works in an attempt to depict the role of cultural markers and in particular, storytelling as a tool that can be wielded towards the preservation of the indigenous Nigerian cultures. The paper specifically argues that storytelling provides a solid basis for raising culturally adjusted individuals and inculcating values or norms that can foster decency, honesty, integrity and creativity in the minds of the young and future generations of Nigerians.